2002
DOI: 10.1126/science.1065507
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and Competition Between Relatives

Abstract: Individuals are predicted to behave more altruistically and less competitively toward their relatives, because they share a relatively high proportion of their genes (e.g., one-half for siblings and one-eighth for cousins). Consequently, by helping a relative reproduce, an individual passes its genes to the next generation, increasing their Darwinian fitness. This idea, termed kin selection, has been applied to a wide range of phenomena in systems ranging from replicating molecules to humans. Nevertheless, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
649
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 709 publications
(669 citation statements)
references
References 44 publications
14
649
2
4
Order By: Relevance
“…In any given population, the fitness of an altruistic gene is dependent on the structure of the population [3,4,27,28]. Our results show that high relatedness can be obtained by structured growth and genetic drift without a small initial group size (figure 2a).…”
Section: Discussionmentioning
confidence: 55%
“…In any given population, the fitness of an altruistic gene is dependent on the structure of the population [3,4,27,28]. Our results show that high relatedness can be obtained by structured growth and genetic drift without a small initial group size (figure 2a).…”
Section: Discussionmentioning
confidence: 55%
“…It has been shown that genetic relatedness alone might be insufficient for maintaining the stable cooperation [36,50], and that repression or policing is also required in the evolution of cooperation [5052]. The necessity of repression or punishment of cheaters or competitors that take food or service without reciprocal reward was widely proven in previous studies [30,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary studies of cooperative interactions have focused on the selective advantages of cooperating, how cooperation is organized, whether cheating a cooperative system can occur, and how cheaters are controlled (4)(5)(6)(7)(8)(9)(10)(11). These studies generally, but not always, focus on within-species interactions and have been behaviorally oriented.…”
mentioning
confidence: 99%